A Semiotics Study on Siwa-Buddha Faith In Blitar East Java The Temples and Their Ornaments: English (ELS Journal on Interdisciplinary Studies in Humanities, 2022)
Brahmaraja Triloka Pura Community as the preserver of the Siwa-Buddha faith has a valuable and important concept depicted through various symbols in its temples. This study aims to reveal the meaning of the temples and their ornaments in the area of Brahmaraja Triloka Pura Community. This study shows that there are main temples in the area, namely Siwa/Daha, Brahma/Jenggala, and Wisnu/Kediri. Then the ornaments found consisted of dragons, makaras, woman statues. Those temples and ornaments symbolize some main concepts of the teachings including Triloka Pura as the last Majapahit, worshiping and respecting ancestors in the sangkan paraning dumadi system, and the combined elements of father and mother in the Siwa-Buddha concept.
Keywords: Semiotics; Siwa-Buddha; Symbols